Effects of the Edaravone, a Drug Approved for the Treatment of Amyotrophic Lateral Sclerosis, on Mitochondrial Function and Neuroprotection - Sun Joo Cha; Kiyoung Kim (Antioxidants, 2022)
Edaravone, the first known free radical scavenger, has demonstrated cellular protective properties in animals and humans. Owing to its antioxidant activity, edaravone modulates oxidative damage in various diseases, especially neurodegenerative diseases. In 2015, edaravone was approved in Japan to treat amyotrophic lateral sclerosis. The distinguishing pathogenic features of neurodegenerative diseases include high reactive oxygen species levels and mitochondrial dysfunction. However, the correlation between mitochondria and edaravone has not been elucidated. This review highlights recent studies on novel therapeutic perspectives of edaravone in terms of its effect on oxidative stress and mitochondrial function.